SUNFLOWER METAPHOR IN DA'WAH THROUGH MUSIC : Analysis of Spirituality and the Meaning of the Song 'Gala Bunga Matahari' by Sal Priadi - Putri Isma Indriyani; Makrifatul Illah (Jurnal Dakwah, 2024)
This study explores da'wah's spiritual and communicative aspects embedded in Sal Priadi's song "Gala Bunga Matahari." The research investigates how the sunflower metaphor is employed to convey themes of loss, hope, and emotional resilience in the context of da'wah through music. Utilizing a qualitative method with textual analysis, the study delves into the lyrical content to uncover the spiritual messages conveyed. The findings indicate that the song effectively serves as a medium for da'wah, facilitating spiritual reflection and providing solace to its listeners. The study concludes that music, as exemplified in this song, can significantly convey da'wah messages by addressing profound emotional and spiritual experiences. [Penelitian ini bertujuan untuk mengeksplorasi aspek spiritual dan komunikatif dakwah yang tertanam dalam lagu "Gala Bunga Matahari" karya Sal Priadi. Penelitian ini menyelidiki bagaimana metafora bunga matahari digunakan untuk menyampaikan tema kehilangan, harapan, dan ketahanan emosional dalam konteks dakwah melalui musik. Dengan menggunakan metode kualitatif melalui analisis teks, penelitian ini mengkaji isi lirik untuk mengungkap pesan spiritual yang disampaikan. Temuan menunjukkan bahwa lagu ini secara efektif berfungsi sebagai media dakwah, memfasilitasi refleksi spiritual dan memberikan penghiburan kepada pendengarnya. Penelitian ini menyimpulkan bahwa musik, seperti yang dicontohkan dalam lagu ini, dapat berperan signifikan dalam menyampaikan pesan dakwah dengan mengatasi pengalaman emosional dan spiritual yang mendalam].